Physio-mechanical and Biological Effects Due to Surface Area Modifications of 3D Printed β-tri- calcium phosphate: An In Vitro Study - Leticia Arbex, MSci; Vasudev Vivekanand Nayak, MSci; John L. Ricci, PhD; Dindo Mijares, DDS, MSci; James E. Smay, PhD; Paulo G. Coelho, MD, DDS, PhD, MBA; Lukasz Witek, MSci, PhD (Annals of 3D Printed Medicine, 2022)
Bone defects are associated with trauma, congenital disorders, non-unions, or infections following surgical procedures. Defects which are unable to heal spontaneously are categorized as “critical sized” and are commonly treated using bone grafts in an effort to facilitate bone regeneration and stabilization. Grafting materials can be either natural or synthetic, each having their respective advantages and disadvantages. Synthetic bone grafts are favored due to their ability to be tailored to exhibit desired properties and geometric configurations. β-tricalcium phosphate (β-TCP) is a synthetic grafting material that has been widely utilized for regenerative purposes due to its favorable osteoconductive properties. In combination with 3D printing, grafting materials can be further customized with respect to their macro and micro features. One way to customize devices is by using 3D printing and varying the surface area, by varying the internal component measurements. The objective of this study was to compare the effect of porosity and surface area of 3D printed β-TCP scaffolds with different strut diameters and the effect on cell proliferation in vitro. ß-TCP scaffolds were printed using a custom-built 3D direct-write micro printer with syringes equipped with different extrusion tip diameters (fdiameter: 200 µm, 250 µm and 330 µm). After sintering and post processing, scaffolds were subjected to micro-computed tomography (µCT) and a Scanning Electron Microscope (SEM) to evaluate surface area and porosity, respectively. Compressive strength was assessed using a universal testing machine. Cell proliferation was assessed through cellular viability, using human osteoprogenitor cells. The surface area of the scaffolds was found to increase with smaller strut diameters. Statistically significant differences (p<0.05) were detected for cellular proliferation, between the smallest extrusion diameter, 200 μm, and the largest diameter, 330 μm, after 48-, 72-, and 168-hours. No statistical significances were detected (p>0.05) with regards to the mechanical properties between groups. This study demonstrated that a smaller diameter rod yielded a higher surface area resulting in increased levels of cellular proliferation. Therefore, tailoring rod dimensions has the capacity to enhance cellular adhesion and ultimately, proliferation.